Melatonin reduces endoplasmic reticulum stress and preserves sirtuin 1 expression in neuronal cells of newborn rats after hypoxia–ischemia. Issue 2 (15th July 2014) - Carloni, Silvia; Albertini, Maria Cristina; Galluzzi, Luca; Buonocore, Giuseppe; Proietti, Fabrizio; Balduini, Walter
Abstract Conditions that interfere with the endoplasmic reticulum (ER) functions cause accumulation of unfolded proteins in the ER lumen, referred to as ER stress, and activate a homeostatic signaling network known as unfolded protein response (UPR). We have previously shown that in neonatal rats subjected to hypoxia–ischemia (HI), melatonin administration significantly reduces brain damage. This study assessed whether attenuation of ER stress is involved in the neuroprotective effect of melatonin after neonatal HI. We found that the UPR was strongly activated after HI. Melatonin significantly reduced the neuron splicing of XBP‐1 mRNA, the increased phosphorylation of eIF2α, and elevated expression of chaperone proteins GRP78 and Hsp70 observed after HI in the brain. CHOP, which plays a convergent role in the UPR, was reduced as well. Melatonin also completely prevented the depletion of SIRT‐1 induced by HI, and this effect was observed in the same neurons that over‐express CHOP. These results demonstrate that melatonin reduces ER stress induced by neonatal HI and preserves SIRT‐1 expression, suggesting that SIRT‐1, due to its action in the modulation of a wide variety of signaling pathways involved in neuroprotection, may play a key role in the reduction of ER stress and neuroprotection observed after melatonin.